Misinterpretation of head and neck masses can delay the correct diagnosis. A two-step demolitive-reconstruction surgery for saving patient's life. (August 2021) - Maranzano, Massimo; D'Ascanio, Luca; Ricci, Giampietro; Omer, Hadeel; Di Stadio, Arianna
Highlights: Correct and early diagnosis is fundamental in head and neck cancer. Some symptoms related to the cancer infiltration can be misdiagnosed. Benign lesion on the face can mask squamous carcinoma and lead to incorrect and tardive diagnosis. Demolitive and Reconstructive surgeries are the option to safe patient's life in case of tardive diagnosis. Abstract: Objective: To present a rare case of sebaceous cyst masking skin squamous carcinoma. The delayed diagnosis made necessary a two-step (demolition and reconstruction) surgery to save patient's life. Material and Methods: A 77-year-old male, suffering from persistent right hemicrania and eye pain referred to different specialists, who misinterpreted his symptoms. The man presented on the right zygomatic area a big sebaceous cyst which masked a squamous cells carcinoma (SCC) infiltrating the surrounding structures including the orbito zygomatic complex and the orbital content that was the cause of the symptoms. Patient underwent biopsy, CT thorax and MRI of the head and neck as pre-operative examinations. A two-step surgery was performed to remove the tumor. Results: The skin biopsy showed the presence of sun damaged skin contains moderately differentiated invasive SCC within the context of sebaceous cyst. While the CT chest was negative, the head and neck MRI showed a huge tumor invading the orbit and periorbital tissue, the zygomatic bone and the soft tissues up to the posterior orbital area, without presence of neck lymph nodes. Le lesion has been classified as cT4 N0 M0 (TNM 8) and a two-step surgery approach (demolition and reconstruction) was performed with successful results at 1 year-follow up. Conclusions: The delayed diagnosis of SCC was due to the misdiagnosis of the signs of the tumor invasion. Demolitive and reconstructive surgeries allowed to preserve patient's life. The careful attention to patient's skin characteristic, the analysis of general and local clinical signs (irradiated pain, cyst and skin type) and the evaluation of the complex differential diagnosis could be the key to avoid delayed treatment in head and neck cancer.